MODAL SOSIAL DALAM MENUNJANG PEMBANGUNAN DI DESA BONO TAPUNG - Tolhas M Simamora; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted in Bono Tapung Village District Tandun Rokan Hulu Riau Province with the problem (1) How is the form of Social Capital that grows and develops in the life of the community in the village of Bono Tapung District Tandun Rokan Hulu? (2) What is the real role of Social Capital in people's lives in Bono Tapung Village, Tandun District, Rokan Hulu Regency in supporting the implementation of village development.. This research aims to find out how the elements of social capital and the form of social capital run in a village, whether it has a significant relationship to the development of village development and to know what the effect of social capital elements on village development. In this study, the study subjects were 5 people. The data collection of research was conducted by interview, observation and documentation of the results of this study explaining that social capital has a very large relationship and impact on the development of Bono Tapung Village. Starting from community relations with the village government, community participation, planning, process, realization. All these things can not be separated from the element of social capital. The result of this study show that the role of social capital is very influential on the development progress of Bono Tapung Village Keywords: Social Capital, Village Development